Sinergi Kementerian Hukum dan HAM serta Komnas HAM dalam Penegakan HAM di Indonesia: Tinjauan Siyāsah Dustūriyyah - Akbar, Muhammad Faris; Khalid, Khalid (MUKADIMAH: Jurnal Pendidikan, Sejarah, dan Ilmu-ilmu Sosial, 2025)
The enforcement of human rights in Indonesia is a vital aspect of the country’s constitutional system, involving multiple institutions with distinct mandates, notably the Ministry of Law and Human Rights and the National Commission on Human Rights (Komnas HAM). This study is driven by concerns over weak coordination and overlapping functions between these two bodies, which hinder the effective protection and enforcement of human rights. The central research question examines how the integration of authority between the Ministry and Komnas HAM can be conceptualized and implemented, viewed through the framework of siyāsah dustūriyyah (Islamic constitutional politics). Using a qualitative method and a normative approach, the study draws on legal texts and Islamic political thought. The findings suggest that, from the perspective of siyāsah dustūriyyah, inter-institutional collaboration in human rights enforcement should be seen as a synergistic exercise of governance aimed at upholding justice and promoting the public good. The study concludes that integrating the roles of the Ministry and Komnas HAM requires a unified model of oversight and policy execution, guided by the Islamic principles of ta‘āwun (mutual cooperation) and al-‘adālah (justice) within the structure of constitutional governance.